Multiplicity of Accounting Concepts and it’s Impact on Thinking and Practical Applications - يحيى عباس حميد; عبد الله بشرى نجم; عبد الحليم صفوان قصي (Journal of Economics and Administrative Sciences, 2012)
مجلة العلوم الاقتصادية والإدارية المجلد 18 العدد 69 الصفحات 318- 332 Accounting profession has been survived for long time and expected to survive in future, with out basing on theory in the field of practical practice . But there are numerous problems which emerge from the practical practice, their solution needs to be based on generally accepted accounting theory. The results of the researches in this field since the beginning of the last century unfolded the difficulty of formulating theory in accounting , but possible to formulate several accounting theories , due to numerous reasons, among them the difficulty of clear identifying of the accounting objectives, and as a result multiplicity of accounting concept which derived from those objectives and constitute a base to accounting principles and standards within the four levels which form the structure of accounting theory . Therefore this research aims at spotlight the levels of accounting theory in general, and the (first and second) levels in particular, with stating the impact of multiplicity of accounting concepts on accounting thought and practical practice .